Functions and mechanisms of epigenetic inheritance in animals. Issue 12 (December 2018) - Skvortsova, Ksenia; Iovino, Nicola; Bogdanović, Ozren
Abstract The idea that epigenetic determinants such as DNA methylation, histone modifications or RNA can be passed to the next generation through meiotic products (gametes) is long standing. Such meiotic epigenetic inheritance (MEI) is fairly common in yeast, plants and nematodes, but its extent in mammals has been much debated. Advances in genomics techniques are now driving the profiling of germline and zygotic epigenomes, thereby improving our understanding of MEI in diverse species. Whereas the role of DNA methylation in MEI remains unclear, insights from genome-wide studies suggest that a previously underappreciated fraction of mammalian genomes bypass epigenetic reprogramming during development. Notably, intergenerational inheritance of histone modifications, tRNA fragments and microRNAs can affect gene regulation in the offspring. It is important to note that MEI in mammals rarely constitutes transgenerational epigenetic inheritance (TEI), which spans multiple generations. In this Review, we discuss the examples of MEI in mammals, including mammalian epigenome reprogramming, and the molecular mechanisms of MEI in vertebrates in general. We also discuss the implications of the inheritance of histone modifications and small RNA for embryogenesis in metazoans, with a particular focus on insights gained from genome-wide studies. Epigenetic profiling of germline and zygotic genomes has revealed that a fraction of mammalian genomes do not undergo epigenetic reprogramming during early development, highlighting the importance of epigenetic inheritance in animals. Inheritance of histone modifications, tRNA fragments and microRNAs can affect gene regulation in the offspring; however, in mammals, epigenetic inheritance rarely operates beyond two generations.